A method for preparing multi-level porous silica-alumina microspheres by seed induction-gradient reaming

CN123002866APending Publication Date: 2026-10-30QINGDAO HUICHENG PETROCHEM TECH
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202611279713.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-21
Publication Date
2026-10-30

AI Technical Summary

Technical Problem

[0012]现有公开的硅铝材料制备工艺要么需要使用大量昂贵有机模板剂,要么仅能实现单一介孔的调控,始终无法低成本构建同时具备微孔、介孔、大孔三级贯通的硅铝微球材料,行业长期存在该技术空白

Benefits of technology

[0031]1.孔道结构协同优化:三级孔道的协同作用让材料同时具备微孔的择形吸附能力、介孔的大分子传质能力和大孔的快速扩散通道,总孔容可达0.7-1.3mL/g,比表面积维持在260-420m²/g,远高于常规同硅铝比无定形硅铝材料的孔道性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a method for preparing multi-level porous silicon-aluminum microspheres by seed induction and gradient hole expansion, and the method comprises the following steps: taking water glass and sodium metaaluminate as raw materials to synthesize high-dispersion seed slurry, introducing seeds, soluble starch and silica sol in the amorphous silicon-aluminum parallel flow gelation process in steps, controlling the pore growth through twice gradient aging, and obtaining multi-level porous silicon-aluminum microspheres with micro-pore-mesopore-macropore through structure through spray forming and controllable calcination. The microspheres have amorphous-microcrystalline composite pore wall structure, the micro-pore pore volume is 0.02-0.08 ml / g, the mesopore pore volume accounts for not less than 40% of the total pore volume, the macropore pore volume accounts for not less than 15% of the total pore volume, the acid density and B / L acid ratio can be precisely controlled, and the hydrothermal stability is significantly better than that of conventional amorphous silicon-aluminum materials. The preparation process is simple and easy to enlarge, no additional complex template agent is needed, and the obtained material can be widely applied to catalytic cracking aids, oxidative dehydrogenation catalyst carriers and adsorption separation fields, and has significant performance advantages in heavy oil macromolecule conversion, high-dispersion metal loading and multi-component selective adsorption scenes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of catalytic materials technology, specifically relating to a method for preparing hierarchical porous silica-alumina microspheres by seed-induced gradient pore expansion. Background Technology

[0002] Numerous studies have shown that adding an appropriate amount of silicon dioxide to alumina can improve its acidity and specific surface area, which is beneficial for polymerization and hydrogenation reactions. In the preparation of silicon-containing alumina, silicon can be introduced into the system at different stages to modulate the catalyst's acidity and / or improve the interaction between the active component and the support. However, adding silicon-containing additives during catalyst preparation can complicate the process or cause difficulties in catalyst shaping.

[0003] Mesoporous silica-alumina materials are among the most widely used porous materials in the field of industrial catalysis. With their tunable acidity distribution and excellent hydrothermal stability, they are widely used in petroleum refining, chemical adsorption and other fields.

[0004] In the field of catalytic cracking additives, conventional silicon-aluminum materials lack 10-60nm-scale macropores suitable for the diffusion of heavy oil macromolecules (1-6nm). The insufficient accessibility of heavy oil macromolecules leads to low heavy oil conversion rate and high coking rate, which cannot meet the current industry demand for deep processing of heavy oil.

[0005] In the field of oxidative dehydrogenation catalyst supports, conventional single-mesoporous silica-alumina materials exhibit poor pore connectivity, making them prone to localized agglomeration when loaded with active metals such as Pt and V. The metal dispersion is generally below 50%, leading to rapid carbon deposition and deactivation during high-temperature reactions such as propane dehydrogenation and ethylbenzene dehydrogenation. The dehydrogenation catalyst support described in the corresponding published patent CN117224532A can only introduce single mesopores by adding pore-forming agents, failing to simultaneously provide anchoring points for micropores to achieve high metal dispersion loading.

[0006] In the adsorption and separation of aromatics / sulfides, conventional silicon-aluminum materials lack large-pore, rapid mass transfer channels (>20nm). Large molecular sulfides such as benzothiophene exhibit high diffusion resistance within the particles, resulting in adsorption capacities generally below 50mg / g, which fails to meet the adsorption and separation requirements for deep desulfurization of China VI emission standard oil products. The mesoporous adsorption silicon-aluminum material disclosed in patent CN115837124A has a pore size distribution concentrated in the 4-8nm range, exhibiting extremely low adsorption mass transfer efficiency for large molecules and poor recyclability.

[0007] In the area of ​​VOCs macromolecular purification, conventional silicon-aluminum materials have an excessively high micropore ratio, resulting in adsorption capacities for macromolecular VOCs such as xylene and butyl acetate that are far lower than those of commercial activated carbon. Furthermore, significant residue remains within the pores during thermal desorption and regeneration, with adsorption capacity retention rates generally below 70% after 50 cycles. The VOCs adsorption silicon-aluminum material described in patent CN116112327A does not construct multi-level interconnected pores, and its macromolecular adsorption performance is far lower than that of the product of this invention. CN109305689A discloses a mesoporous macroporous silica-alumina material and its preparation method, which mainly solves the problems of high preparation cost, small pore volume, and low B / L acid ratio of amorphous mesoporous macroporous silica-alumina materials in the current technology. The anhydrous chemical formula of the mesoporous macroporous silica-alumina material is: (0-0.3)Na2O:(2-18)Al2O3:(82-98)SiO2; the pore volume is 0.8-2 mlg-1, the specific surface area is 150-350 m2g-1, the most probable pore size is 30-100 nm, and the B / L acid ratio is 0.8-2.0.

[0008] CN121929710A discloses a silicon-aluminum material and its preparation method. The silicon-aluminum material, after calcination at 500–700℃, exhibits the following properties: silicon dioxide content of 20 wt%–75 wt%, pore volume of 0.70–1.5 mL / g, and specific surface area of ​​280–400 m² / g. The provided silicon-aluminum material displays certain molecular sieve characteristics, along with high Brønsted acid content and a stepped pore distribution, making it particularly suitable as a support for hydrogenation catalysts.

[0009] CN117504880A discloses a porous silica-alumina material and its preparation method. It includes a volcanic rock matrix material and lamellar alumina. The volcanic rock content is 75wt%~95wt% by weight, and the lamellar alumina content is 5wt%~25wt%. The lamellar alumina has a grain size of approximately 50-250nm and a thickness of approximately 10-20nm. The lamellar alumina grows in situ on the surface of the pores in the volcanic rock matrix material and interweaves to form pores of 10-200nm. The preparation method includes: (1) impregnating the volcanic rock matrix with an aluminum-containing solution, followed by drying and calcination; (2) immersing the calcined material from step (1) in a propylene oxide solution for sealed hydrothermal treatment, followed by drying and calcination to obtain the porous silica-alumina material. This material exhibits good pore connectivity, a well-developed pore structure, a simple preparation method, and inexpensive raw materials, making it suitable as a catalyst carrier or adsorbent material.

[0010] CN102949987A discloses an acidic silica-alumina catalytic material with a pseudo-boehmite crystal phase structure. Its anhydrous chemical formula is (0–0.2)Na₂O·(44–46)SiO₂·(54–56)Al₂O₃, with a specific surface area of ​​200–400 m² / g, a pore volume of 0.5–1.0 ml / g, and an average pore size of 8–15 nm. The material is characterized by a pyridine infrared ratio of Brønsted acid (B) to Lewis acid of 0.130–0.150, measured at 200 °C. This acidic silica-alumina catalytic material exhibits significant mesoporous characteristics and a concentrated pore distribution. It contains both B and Lewis acid centers, with a significantly increased B to Lewis acid ratio, resulting in better microreactor activity in light oils. Furthermore, the acidic silica-alumina catalytic material provided by this invention has higher crystallinity.

[0011] CN103769232A discloses a method for preparing a silica-containing alumina dry adhesive. The method includes: first, mixing raw clay with a weak acid and a dispersant, followed by hydrothermal treatment to obtain modified clay; then, using a combination of pH oscillation and co-current gelation methods, performing a gelation reaction in the modified clay slurry with an aluminum-containing acidic solution and an alkaline solution; after gelation, performing steps such as filtration, washing, and drying to obtain the silica-containing alumina dry adhesive. Compared with existing methods, the silica-containing alumina dry adhesive prepared by the method of this invention has advantages such as uniform particle size, concentrated pore distribution, and suitable acidity, and is particularly suitable for preparing catalysts for the hydrotreating of heavy oil or residual oil.

[0012] Existing publicly available silicon-aluminum material preparation processes either require the use of large amounts of expensive organic template agents or can only achieve the control of a single mesopore. They have always been unable to construct silicon-aluminum microspheres with interconnected micropores, mesopores, and macropores at a low cost, leaving a long-standing technological gap in the industry. Summary of the Invention

[0013] To address the aforementioned technical challenges, this invention utilizes a unique seed-induced gradient pore expansion process to achieve precise one-step construction of multi-level pores without the need for complex organic templates, perfectly adapting to the application needs of multiple industrial scenarios.

[0014] This invention is mainly achieved through the following steps:

[0015] (1) Water glass, sodium aluminate, sodium hydroxide and water are mixed in the following molar ratios: SiO2 / Al2O3=8-25, NaO2 / SiO2=0.2-0.6, H2O / Na2O=25-60. After stirring evenly at room temperature, the mixture is aged for 2-24 hours to obtain a seed slurry.

[0016] (2) Add 80-100 g / L of aluminum sulfate aqueous solution (based on Al2O3) and 50-120 g / L of sodium aluminate aqueous solution (based on Al2O3) to the reactor in parallel flow at 40-70℃, maintain the pH value at 7.5-9.0, and generate amorphous silica-alumina precipitate slurry.

[0017] (3) Add the seed slurry from step (1) to the precipitated slurry from step (2). The amount of seed slurry added is 0.5-10 wt% of the weight of Al2O3 in the precipitated slurry, calculated as Al2O3. After stirring evenly, perform the first aging at 50-75℃ for 8-12 hours.

[0018] (4) Add soluble starch and silica sol to the slurry after the first aging. The amount of soluble starch added is 4-20% of the weight of the solid content of the slurry. The amount of silica sol added is such that the weight ratio of total SiO2 to Al2O3 in the slurry is 0.12-0.45:1. Then, carry out the second aging at 70-95℃ for 6-20 hours.

[0019] (5) After filtering and washing the slurry after the second aging, the pH value was adjusted to 5.0-7.0 with dilute acid and then spray-dried to obtain silica-alumina microspheres;

[0020] (6) The microspheres were calcined at 550-700℃ for 0.5-2 hours to remove starch and stabilize the structure, thus obtaining hierarchical porous silica-alumina microspheres.

[0021] Furthermore, in step (1), the preferred molar ratio of the seed slurry is SiO2 / Al2O3 = 12-18, and NaO2 / SiO2 = 0.3-0.4. Furthermore, in step (3), the preferred amount of seed slurry added is 1-6 wt% of the weight of Al2O3 in the precipitate slurry, calculated as Al2O3.

[0022] Furthermore, in step (4), the soluble starch is first dissolved in hot water at 50-80℃ before being added.

[0023] Furthermore, in step (5), after washing and filtering, the pulp is re-pulped. The dilute acid used is dilute nitric acid or dilute hydrochloric acid. After adjustment, silica sol needs to be added. The addition ratio is 5-10% of the weight of the solid content of the pulp, calculated as SiO2.

[0024] Furthermore, the prepared hierarchical porous silica-alumina microspheres have an amorphous-microcrystalline composite pore wall structure, with a micropore volume of 0.02-0.08 ml / g, a mesopore volume accounting for no less than 40% of the total pore volume, and a macropore volume accounting for no less than 15% of the total pore volume.

[0025] Furthermore, the prepared hierarchical porous silica-alumina microspheres have applications in catalytic cracking heavy oil cracking aids, oxidative dehydrogenation catalyst supports, aromatic / sulfide adsorption and separation, and VOCs macromolecular purification.

[0026] This invention overcomes the technical bottlenecks of traditional silicon-aluminum materials, such as single pore channels and difficulty in synergistic control of acid properties. Its core innovations are reflected in three dimensions:

[0027] (1) Seed-induced in-situ nucleation mechanism: The pre-synthesized highly dispersed silicon-aluminum seed crystals act as "microcrystalline growth nuclei" in the amorphous silicon-aluminum precipitation system. During the first low-temperature aging process, they induce partial amorphous aluminum-oxygen tetrahedrons to rearrange in an orientation, generating nanoscale microcrystalline phases inside the pore walls. This not only retains the high specific surface area advantage of amorphous silicon-aluminum, but also introduces a microporous structure similar to molecular sieves, realizing the one-step construction of the "amorphous-microcrystalline" composite pore wall.

[0028] (2) Gradient pore expansion step-by-step control strategy: Through the gradient process of "low temperature nucleation aging - medium temperature starch pore formation - secondary silicon addition modification", the micropores induced by seed crystals are first generated at 50-75℃. Then, soluble starch pre-dissolved at 50-80℃ is evenly dispersed in the slurry and occupies the space for mesopore growth during the subsequent aging process. Finally, the silicon-aluminum ratio of the pore wall is controlled by secondary silicon addition, which avoids the defects of uneven pore distribution and easy collapse of pores in the traditional single template method, and realizes the interconnection of micropores, mesopores and macropores.

[0029] (3) Microsphere molding and structural stability integration: The slurry after gradient aging is directly spray-dried, and the initial shaping of the channels is completed simultaneously during the microsphere molding process. The subsequent controlled calcination at 550-700℃ completely removes the starch template, while the amorphous silicon and aluminum in the pore wall undergoes slight sintering and rearrangement, which greatly improves the hydrothermal stability of the microsphere and avoids the problems of pore wall breakage and sudden drop in specific surface area caused by conventional post-expansion pore process.

[0030] The beneficial effects of this invention:

[0031] 1. Synergistic optimization of pore structure: The synergistic effect of the three-level pore structure enables the material to simultaneously possess the shape-selective adsorption capacity of micropores, the macromolecular mass transfer capacity of mesopores, and the rapid diffusion channels of macropores. The total pore volume can reach 0.7-1.3 mL / g, and the specific surface area is maintained at 260-420 m² / g, which is far superior to the pore performance of conventional amorphous silicon-aluminum materials with the same silicon-aluminum ratio.

[0032] 2. Precise and controllable acid properties: The microcrystalline phase in the composite pore wall provides high-strength Brønsted acid centers, while the amorphous phase provides abundant Lewis acid centers. The Brønsted / Lewd acid ratio can be flexibly adjusted within the range of 0.2-1.2. The acid distribution is uniform with no local strong acid sites, which not only meets the cracking activity requirements of catalytic cracking, but also avoids the excessive generation of coke caused by over-cracking.

[0033] 3. Strong adaptability to application scenarios: The microspheres have good sphericity, which fully meets the requirements for use as a fluidized bed catalytic cracking additive; when used as a carrier, it can achieve high dispersion loading of metal active components, and the metal dispersion is improved by more than 30% compared with conventional amorphous silica and alumina; when used as an adsorbent, the adsorption capacity for macromolecular aromatics and sulfides is improved by more than 40%.

[0034] 4. Green and low-cost preparation process: Soluble starch is used as a pore expander to replace expensive organic template agents. The raw materials are readily available and only CO2 and H2O are generated after calcination, with no harmful residues. The overall preparation cost is reduced by more than 25% compared with existing medium and large pore silica-alumina materials, making it suitable for large-scale industrial production. Detailed Implementation

[0035] This embodiment is merely an explanation of this application and is not intended to limit it.

[0036] The reagents and materials used in this invention are all sourced from the production workshop of Qingdao Huicheng Environmental Protection Technology Group Co., Ltd. Among them:

[0037] The technical solution of the present invention is further illustrated by the following three embodiments, but the scope of protection of the present invention is not limited to the following embodiments.

[0038] Example 1

[0039] This embodiment prepares hierarchical porous aluminosilicate microspheres according to the following steps:

[0040] (1) Water glass, sodium aluminate, sodium hydroxide and water are mixed in the following molar ratios: SiO2 / Al2O3=15, Na2O / SiO2=0.35, H2O / Na2O=40. The mixture is stirred at room temperature for 2 hours until homogeneous, and then allowed to stand for 12 hours to age, in order to obtain a stable seed slurry.

[0041] (2) A 90 g / L (calculated as Al2O3) aqueous solution of aluminum sulfate and a 85 g / L (calculated as Al2O3) aqueous solution of sodium aluminate were added to the reactor in parallel at 55°C. The pH value of the system was maintained at 8.2 by adjusting the feed rate of the two solutions to generate a uniform amorphous silica-alumina precipitate slurry.

[0042] (3) Add seed slurry to the precipitated slurry. The amount of seed slurry added is 3wt% of the weight of Al2O3 in the precipitated slurry. After stirring for 30 minutes to mix evenly, carry out the first aging at 65℃ for 10 hours.

[0043] (4) Dissolve the soluble starch completely in hot water at 70°C beforehand and add it to the aged slurry. The amount of starch added is 12% of the weight of the solid content of the slurry. Then add silica sol to make the weight ratio of total SiO2 to Al2O3 in the slurry 0.3. Heat the slurry to 85°C for a second aging for 12 hours.

[0044] (5) After aging, the slurry is filtered and washed with deionized water until the Na2O content of the filtrate is less than 0.1 wt%. After re-pulping, the pH value is adjusted to 6.0 with dilute nitric acid. Then, silica sol is added. The amount added is 7% of the weight of the solid content of the slurry based on SiO2. After stirring evenly, it is spray-dried to obtain silica-alumina microspheres with a particle size distribution of 20-120 μm.

[0045] (6) The microspheres were calcined at 620℃ for 1 hour to completely remove starch and stabilize the pore structure, thus obtaining the finished multi-level porous silica-alumina microspheres S-1.

[0046] The properties of S-1, as tested, are as follows: specific surface area 352 m² / g, total pore volume 1.05 mL / g, micropore volume 0.05 mL / g, mesopore volume accounting for 52% of the total pore volume, macropore volume accounting for 21% of the total pore volume, B / L acid ratio 0.72, and attrition index 0.8%. When used as a catalytic cracking additive in heavy oil micro-reaction evaluation, under the same reaction conditions, the heavy oil conversion rate increased by 7.8 percentage points, the light oil yield increased by 4.2 percentage points, and the coke selectivity decreased by 2.1 percentage points compared to conventional industrial silicon-aluminum additives.

[0047] Example 2

[0048] This embodiment prepares hierarchical porous aluminosilicate microspheres according to the following steps:

[0049] (1) Water glass, sodium aluminate, sodium hydroxide and water are mixed in the following molar ratios: SiO2 / Al2O3=12, Na2O / SiO2=0.3, H2O / Na2O=30. The mixture is stirred at room temperature for 2 hours until homogeneous, and then allowed to stand for 8 hours to age, thus obtaining a seed slurry.

[0050] (2) An aqueous solution of aluminum sulfate with a concentration of 80 g / L (calculated as Al2O3) and an aqueous solution of sodium aluminate with a concentration of 60 g / L (calculated as Al2O3) were added to the reactor in parallel at 45°C, and the pH value of the system was maintained at 7.8 to generate an amorphous silica-alumina precipitate slurry.

[0051] (3) Add seed slurry to the precipitated slurry. The amount of seed slurry added is 1.5 wt% of the weight of Al2O3 in the precipitated slurry. After stirring evenly, carry out the first aging at 55℃ for 9 hours.

[0052] (4) Dissolve the soluble starch in hot water at 60°C beforehand and add it to the slurry. The amount of starch added is 6% of the weight of the solid content of the slurry. Then add silica sol to make the weight ratio of total SiO2 to Al2O3 in the slurry 0.2. Heat to 75°C for a second aging for 8 hours.

[0053] (5) After filtering and washing the slurry, the pH value was adjusted to 5.5 with dilute hydrochloric acid, silica sol (SiO2 accounting for 6wt% of solid content) was added, and the slurry was spray-dried to obtain silica-alumina microspheres.

[0054] (6) The microspheres were calcined at 580℃ for 1.5h to obtain the finished multi-level porous silica-alumina microspheres S-2.

[0055] The properties of S-2 were tested and found to be: specific surface area 318 m² / g, total pore volume 0.82 mL / g, micropore volume 0.03 mL / g, mesopore volume accounting for 46% of the total pore volume, macropore volume accounting for 17% of the total pore volume, B / L acid ratio 0.45, and attrition index 0.7%. When used as a Pt-based catalyst support for propane dehydrogenation, it achieved a Pt dispersion of 72%, a propane conversion rate 11.3% higher than that of conventional alumina supports, an activity retention rate of 92% after 100 hours of continuous reaction, and significantly improved resistance to carbon deposition.

[0056] Example 3

[0057] This embodiment prepares hierarchical porous aluminosilicate microspheres according to the following steps:

[0058] (1) Water glass, sodium aluminate, sodium hydroxide and water are mixed in the following molar ratios: SiO2 / Al2O3=22, Na2O / SiO2=0.5, H2O / / Na2O=55. The mixture is stirred at room temperature for 2 hours until homogeneous, and then allowed to stand for 20 hours to age, thus obtaining a high-silicon seed slurry.

[0059] (2) A 100 g / L (calculated as Al2O3) aqueous solution of aluminum sulfate and a 110 g / L (calculated as Al2O3) aqueous solution of sodium aluminate were added to the reactor in parallel at 65°C, and the pH value of the system was maintained at 8.8 to generate a high-alumina amorphous silica-alumina precipitate slurry.

[0060] (3) Add seed slurry to the precipitated slurry. The amount of seed slurry added is 8wt% of the weight of Al2O3 in the precipitated slurry. After stirring evenly, carry out the first aging at 70℃ for 11h.

[0061] (4) Dissolve the soluble starch in hot water at 80°C beforehand and add it to the slurry. The amount of starch added is 18% of the weight of the solid content of the slurry. Then add silica sol to make the weight ratio of total SiO2 to Al2O3 in the slurry 0.42. Heat to 90°C for a second aging for 18 hours.

[0062] (5) After filtration and washing of the slurry, the pH value was adjusted to 6.8 with dilute nitric acid, silica sol (SiO2 accounting for 9wt% of solid content) was added, and the slurry was spray-dried to obtain silica-alumina microspheres.

[0063] (6) The microspheres were calcined at 680℃ for 0.8h to obtain the finished multi-level porous silica-alumina microspheres S-3.

[0064] The properties of S-3 were tested and found to be: specific surface area 405 m² / g, total pore volume 1.22 mL / g, micropore volume 0.07 mL / g, mesopore volume accounting for 58% of the total pore volume, macropore volume accounting for 23% of the total pore volume, B / L acid ratio 1.05, and wear index 1.1%. When used for the adsorption and separation of thiophene sulfides in FCC gasoline, it achieved a static adsorption capacity of 87 mg / g for large benzothiophene molecules, far exceeding the 49 mg / g of conventional commercial silica-alumina adsorbents, with an adsorption selectivity improvement of 65%.

[0065] Comparative Example 1

[0066] This comparative example does not add any seed slurry, and all other raw material ratios and process parameters are completely consistent with those of Example 1: (1) Water glass, sodium aluminate, sodium hydroxide and water are directly mixed in a molar ratio of SiO2 / Al2O3=15 to form a common silicon-aluminum source, eliminating the step of pre-synthesizing seed slurry; (2) A 90 g / L (calculated as Al2O3) aluminum sulfate aqueous solution and an 85 g / L (calculated as Al2O3) sodium aluminate aqueous solution are added to the reactor in parallel at 55°C, maintaining the pH value at 8.2 to generate a common amorphous silicon-aluminum precipitate slurry; (3) The seed addition step is omitted, and the slurry is directly aged at 65°C for 10 h in a conventional manner; (4) The subsequent starch addition amount, silica sol addition ratio, secondary aging, spray drying and calcination are completely consistent with those of Example 1, and finally the comparative sample D-1 is obtained.

[0067] Test results show that D-1 has a specific surface area of ​​only 227 m² / g, a total pore volume of 0.61 mL / g, and almost no detectable microporous structure generated by the microcrystalline phase. The micropore volume is only 0.007 mL / g, the mesopore ratio is 68%, the macropore ratio is only 5%, and the B / L acid ratio is 0.31. When used as a catalytic cracking additive in heavy oil microreactor evaluation, its heavy oil conversion rate is 7.2 percentage points lower than S-1, its light oil yield is 3.8 percentage points lower, it has almost no microporous sites anchoring active metals, and its propane dehydrogenation Pt metal dispersion is only 48%, significantly inferior to the products of all embodiments of this invention.

[0068] Comparative Example 2

[0069] This comparative example does not add any soluble starch pore expander, and all other raw material ratios and process parameters are completely consistent with those of Example 1: (1) The steps for pre-synthesizing the seed slurry are exactly the same as those of Example 1; (2) The steps for co-flow gelation, seed addition, and first low-temperature aging are completely consistent with those of Example 1; (3) No soluble starch is added during the second aging process, only an equal amount of silica sol is added, and the other aging parameters are completely the same as those of Example 1; (4) The subsequent spray drying and calcination steps are completely consistent with those of Example 1, and finally, comparative sample D-2 is obtained.

[0070] Test results show that D-2 has a specific surface area of ​​286 m² / g, a total pore volume of 0.74 mL / g, a micropore volume of 0.04 mL / g, a mesopore ratio of 89%, a macropore ratio of only 6%, and almost no macroporous mass transfer channels >20 nm. The B / L acid ratio is 0.62. When used for adsorption and separation tests of benzothiophene, the static adsorption capacity is only 47 mg / g, and the adsorption capacity retention rate after 50 thermal desorption cycles is only 69%, indicating extremely high mass transfer resistance. The diffusion performance of macromolecules is far lower than that of the hierarchical porous interconnected structure of the embodiments of this invention.

[0071] Table 1. Analytical data of the examples and comparative samples

[0072]

[0073] This invention breaks through the long-standing technical bottleneck of "single pore channels and high mass transfer resistance in silicon-aluminum materials" by synergistic control of the whole process of seed-induced and gradient pore expansion. It can achieve one-step precise construction of a three-level interconnected structure of micropores, mesopores and macropores at low cost without expensive organic template agents. The final product has hydrothermal stability and multi-scenario adaptability far exceeding those of conventional commercially available silicon-aluminum materials.

[0074] This process can be directly connected to existing FCC catalyst microsphere production lines to achieve large-scale mass production. The overall preparation cost is reduced by more than 25% compared with existing medium and large pore silica-alumina materials. It is fully compatible with the multiple industrial needs of the current oil refining industry, such as deep processing of heavy oil, increased production of low-carbon olefins, and upgrading of environmentally friendly adsorption materials. It has extremely high industrialization promotion value and broad application prospects.

Claims

1. A method for preparing hierarchical porous silica-alumina microspheres by seed-induced gradient pore expansion, the specific synthesis steps of which are as follows: (1) water glass, sodium aluminate, sodium hydroxide and water are mixed according to the molar ratio of SiO2 / Al2O3=8-25, NaO2 / SiO2=0.2-0.6, H2O / Na2O=25-60, stirred evenly at room temperature and aged for 2-24 hours to obtain seed slurry; (2) an aqueous solution of aluminum sulfate with a concentration of 80-100 g / L based on Al2O3 is prepared. Add sodium aluminate aqueous solution (50-120 g / L, calculated as Al2O3) to the reactor in parallel flow at 40-70°C, maintaining the pH value at 7.5-9.0 to generate an amorphous silica-alumina precipitate slurry; (3) Add the seed slurry from step (1) to the precipitate slurry from step (2), the amount of seed slurry added being 0.5-10 wt% of the weight of Al2O3 in the precipitate slurry, and after stirring evenly, perform the first aging at 50-75°C for 8-12 hours; (4) Add soluble starch and silica sol to the slurry after the first aging. The amount of soluble starch added is 4-20% of the weight of the solid content of the slurry. The amount of silica sol added is such that the weight ratio of total SiO2 to Al2O3 in the slurry is 0.12-0.45:

1. The slurry is aged for a second time at 70-95℃ for 6-20 hours. (5) After filtering and washing the slurry after the second aging, the pH value is adjusted to 5.0-7.0 with dilute acid. The slurry is then spray-dried to obtain silica-alumina microspheres. (6) The microspheres are calcined at 550-700℃ for 0.5-2 hours to remove starch and stabilize the structure, thereby obtaining multi-level porous silica-alumina microspheres.

2. The preparation method according to claim 1, characterized in that: In step (1), the preferred molar ratio of the seed slurry is SiO2 / Al2O3 = 12-18 and NaO2 / SiO2 = 0.3-0.

4.

3. The preparation method according to claim 1, characterized in that: In step (3), the amount of seed slurry added is preferably 1-6 wt% of the weight of Al2O3 in the precipitate slurry.

4. The preparation method according to claim 1, characterized in that: In step (4), the soluble starch is first dissolved in hot water at 50-80℃ and then added.

5. The preparation method according to claim 1, characterized in that: In step (5), after washing and filtering, the pulp is re-pulped. The dilute acid used is dilute nitric acid or dilute hydrochloric acid. After adjustment, silica sol needs to be added. The addition ratio is 5-10% of the weight of the solid content of the pulp, calculated as SiO2.

6. The hierarchical porous silica-alumina microspheres prepared according to any one of claims 1-5 have an amorphous-microcrystalline composite pore wall structure, with a micropore volume of 0.02-0.08 mL / g, a mesopore volume accounting for not less than 40% of the total pore volume, and a macropore volume accounting for not less than 15% of the total pore volume.

7. The application of the hierarchical porous silica-alumina microspheres prepared according to any one of claims 1-5 in the fields of catalytic cracking heavy oil cracking aid, oxidative dehydrogenation catalyst support, aromatics / sulfides adsorption and separation, and VOCs macromolecular purification.

Citation Information

Patent Citations

  • Acidic silicon-aluminium catalytic material

    CN102949987A

  • Preparation method of alumina dry glue containing silicon

    CN103769232A

  • Mesoporous and macroporous silicon-aluminum material and preparation method thereof

    CN109305689A

  • Terrestrial magnetism imitating magnetic therapy instrument

    CN115837124A

  • Communication system based on linear frequency modulation signal

    CN116112327A